Tanggung Jawab Sosial Sesama Manusia Dalam Kode Etika Perusahaan - Prabowo, Eko; Mahmud, Hamidullah (Sahabat Publikasi, 2024)
This article discusses the social responsibilities of fellow humans in the company code of ethics. The aim of this research is to find out the social responsibilities of fellow humans in the code of ethics. Responsibility of fellow humans is important for everyday life. A code of ethics can also be known as a pattern of rules or procedures for carrying out activities within a company. This guideline applies to all aspects of human behavior in everyday life. Discussions about ethics and human responsibility can be carried out because they can be unethical, and there is a lot of evidence such as currently regarding responsibility in unethical companies. The method used in this research to analyze the social responsibility of fellow humans in ethics is descriptive qualitative research. Corporate social responsibility (CSR) is a sustainable effort to act in accordance with a code of ethics and hopes to contribute to the development of society and the company.